RURAL SCHOLARSHIP SCHEMES A solution to the human resource crisis in rural district hospitals? - A.J. Ross; I.D. Couper (South African Family Practice)
Recruiting sufficient health personnel for rural hospitals is an ongoing problem. The Friends of Mosvold Scholarship Scheme in northern KwaZulu-Natal is a locally based scholarship scheme that offers the local community a chance to develop its own human resources for health care. Students are required to work in the local hospital during their vacations and sign a contract to work back their scholarship year for year. Already 44 people from Ingwavuma are being supported to study for a variety of health professions. This concept is being extended to the Limpopo and North-West provinces through the Wits Initiative for Rural Health Education. The scheme provides a model for human resource development at a district level that could be usefully adopted by any tier of government.